PROGRAM PECAHAN LINEAR - Endarwati, Erlin Dwi; Khabibah, Siti; ., Farikhin (MATEMATIKA, 2014)
. Linear Fractional Programming (LFP) problem is general form of Linear Programming (LP) problem. LFP problem arise when there is requirement to optimalize the efficiency of some activity. The efficiency related to the most productive way to use the scarce resources. Many method have been published to solve LFP problem. In this final project explained two methods, Charnes-Cooper’s method and Hasan-Acharjee’s method. The both method use a transformation to change LFP problem become LP problem, then solved by simplex method. Finally, it is concluded that there is comparison that the Charnes-Cooper’s method can be applied in all of LFP form which the set of feasible solutions is non-empty and bounded, but the formed LP becoming more complex than Hasan-Acharjee’s method. Hasan-Acharjee’s method cannot be used when the constanta of denominator in objective function is zero.